Chronic pain in the 11th revision of the International Classification of Diseases: users' questions answered : special article: ICD-11 and chronic pain - Korwisi, Beatrice; Barke, Antonia; Rief, Winfried; Treede, Rolf-Detlef; Kleinstäuber, Maria (Pain, 2022)
For the first time, the upcoming International Classification of Diseases and Related Health Problems, Eleventh Revision (ICD-11) will include a comprehensive classification of chronic pain, which is based on the biopsychosocial definition of chronic pain. This presents a great opportunity for pain research and clinical practice. The new classification consists of 7 main diagnostic categories of chronic pain, which are further divided into increasingly specific levels of diagnoses. Each diagnosis is characterized by clearly defined operationalized criteria. Future users will need to familiarize themselves with the new system and its application. The aim of the present publication is to provide users of the ICD-11 chronic pain classification with answers to frequently asked questions regarding the ICD-11 as a whole, the ICD-11 chronic pain classification, and its application to common pain syndromes. The questions compiled in this study reached the International Association for the Study of Pain Task Force through different routes (eg, at conferences, by letter, or during field testing). Furthermore, the authors collected questions posted to the ICD-11 browser and contacted early users of the classification to enquire about their most frequent difficulties when applying the new diagnoses. The authors of the present publication prepared answers to these frequently asked questions. This publication intends to act as a guide for the future users of the new ICD-11 chronic pain classification, hence facilitating its implementation.
Online verfügbar: 3 December 2021
Gesehen am 25.09.2023